2020
DOI: 10.1093/mnras/staa2582
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of LTE and NLTE synthetic stellar spectra in a machine learning framework

Abstract: In the current era of stellar spectroscopic surveys, synthetic spectral libraries are the basis for the derivation of stellar parameters and chemical abundances. In this paper, we compare the stellar parameters determined using five popular synthetic spectral grids (INTRIGOSS, FERRE, AMBRE, PHOENIX, and MPIA/1DNLTE) with our convolutional neural network (CNN, StarNet). The stellar parameters are determined for six physical properties (effective temperature, surface gravity, metallicity, [α/Fe], radial velocity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Some experiments are conducted on the reference data (section 2), RRNet shows good performance on them. In addition, RRNet has higher accuracy and better generalization capability compared to the typical models such as StarNet (Fabbro et al 2017;Bialek et al 2020).…”
Section: A Rrnet Model For Spectral Parameter Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some experiments are conducted on the reference data (section 2), RRNet shows good performance on them. In addition, RRNet has higher accuracy and better generalization capability compared to the typical models such as StarNet (Fabbro et al 2017;Bialek et al 2020).…”
Section: A Rrnet Model For Spectral Parameter Estimationmentioning
confidence: 99%
“…This kind methods usually estimate parameters by approximating the mapping relationship from observed spectra to stellar parameters (e.g. Fabbro et al 2017;Bialek et al 2020;Leung & Bovy 2018;Wang et al 2020), or from stellar parameters to observed spectra (e.g. Ting et al 2019;Xiang et al 2019;Rui et al 2019) using neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…The previous works assumed that the approximations of LTE and hydrostatic equilibrium hold. These kinds of equilibrium have been questioned, and including the non-LTE effects has often modified and improved results of spectroscopic analysis (e.g., Asplund 2005;Bergemann et al 2019;Amarsi et al 2020;Bialek et al 2020). Moreover, it has been demonstrated that significant non-LTE effects appear in some Fe lines (Bergemann et al 2012) and Ca lines (Osorio et al 2019) that are located within the wavelength range of our interest.…”
Section: Comparison With Other Gravity Scalesmentioning
confidence: 99%
“…With the arrival of artificial intelligence and the big data era, deep-learning methods have been attempted to deal with the estimation of stellar parameters. These kinds of methods usually estimate parameters by approximating the mapping relationship from observed spectra to stellar parameters (e.g., Fabbro et al 2017;Leung & Bovy 2018;Bialek et al 2020;Wang et al 2020), or from stellar parameters to observed spectra (e.g., Rui et al 2019;Ting et al 2019;Xiang et al 2019) using neural networks. However, most of the above models use simple fully connected neural networks or convolutional neural networks to establish mapping relationships.…”
Section: Introductionmentioning
confidence: 99%